Hospitalizations for infections by age and sex: register-based study of Danish children 1977–2014. Issue 2 (1st February 2020) - Larsen, Jacob W. W.; Sørensen, Anders F.; Jensen, Aksel K. G.; Poulsen, Anja; Gehrt, Lise; Benn, Christine S.; Sørup, Signe
Abstract: Background: Infectious diseases are a major cause of hospitalizations in children and there is increasing interest in sex differences in immunity during childhood. Therefore, we examined hospital admission rates for infectious diseases in Danish children by age and sex. Methods: Register-based cohort study of all Danish residents aged 0–14 years from 1977 to 2014. We examined total admission rate for infections and rates of admission by types of infection. Results: This study included 3, 689, 999 children and 1, 080, 750 admissions for infections. The admission rates peaked at age 0 months (boys, 197.9 admissions per 1000 person-years; girls, 160.9) and age 11 months (boys, 155.5; girls, 113.9). The male–female ratio of admissions was 1.25 for children aged 0–14 years, but varied by age and type of infection. Boys had the highest admission rate for any infection until 9 years of age after which girls had a higher rate. Boys had higher admission rates for gastrointestinal infections and lower respiratory tract infections than girls at all ages. The admission rates for upper respiratory tract infections and 'Other infections' for girls were higher than the rates for boys at age 10 and 4 years, respectively. Conclusions: Overall, boys had around 25% higher admission rates for infections than girls, with some variation according to age and type of infection.